2021
DOI: 10.1097/acm.0000000000004212
|View full text |Cite
|
Sign up to set email alerts
|

Is Academic Attainment or Situational Judgment Test Performance in Medical School Associated With the Likelihood of Disciplinary Action? A National Retrospective Cohort Study

Abstract: Change controlVersion 5 1 Version 5 of this document contains changes to:1.1 Who can apply for a dataset (paragraphs 15 and 16). Information for student applicants 1.2 Stage 7 -Software arrangements and configuring the Safe Haven (paragraphs 44 -48). To improve data management data extracts will now be provided to researchers as a database in the Safe Haven. GMC staff will be able to assist researchers with connecting to analysis packages to their research extract database. 1.3Stage 8 -Review of analysis outpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
9
1
Order By: Relevance
“…15,16 These studies reported univariable relationships between the SJT scores and misconduct in both medical students 15 and during the first 5 years of practice. 16 However, in both cases, these relationships were no longer statistically significant after adjusting for the influence of educational and demographic factors. Neither study reported results solely adjusted for performance on other selection metrics.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…15,16 These studies reported univariable relationships between the SJT scores and misconduct in both medical students 15 and during the first 5 years of practice. 16 However, in both cases, these relationships were no longer statistically significant after adjusting for the influence of educational and demographic factors. Neither study reported results solely adjusted for performance on other selection metrics.…”
Section: Discussionmentioning
confidence: 98%
“…Likewise, two previous studies, both using data from the UKMED, explored the relationship between performance on an SJT taken after medical school entry and disciplinary action 15,16 . These studies reported univariable relationships between the SJT scores and misconduct in both medical students 15 and during the first 5 years of practice 16 . However, in both cases, these relationships were no longer statistically significant after adjusting for the influence of educational and demographic factors.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations